Performance-Related Material Properties of Asphalt Mixture Components - Ling, Meng; Zhang, Yao; Ding, Haibo; Chen, Yu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains the most recent research in pavement engineering, which mainly addresses the performance-related properties of asphalt mixtures. We hope that this reprint is helpful for researchers and pavement industries to generate a better and deeper understanding of pavement materials, pavement construction, and pavement maintenance.